Water supply and sewerage - McGhee, Terence J. (McGraw Hill, 2007)
Intended to introduce the design of water and wastewater treatment systems, the text incorporates recent improvements in our understanding of fundamental phenomena applications of new technologies and materials and new computational techniques. The book can also be used to introduce engineers to the design of hydraulic networks